2005
DOI: 10.5713/ajas.2006.280
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stress Related Genes on Carcass Traits and Meat Quality in Pigs

Abstract: The current study was conducted to investigate the relationship between stress related gene and meat quality in pigs. A total number of 212 three-way cross bred (Landrace-Yorkshire×Duroc) and 38 Duroc were sampled from the Korean pig industry to determine genotype frequency of porcine stress syndrome (PSS) and heat shock protein 70 kDa (HSP70) genes and their relationship with carcass traits and longissimus meat quality. Screen of HSP70 was performed by the single strand conformation polymorphism (SSCP) techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Overexpression of the HSP70.2 in EM and IC in the present study could be also related to the quantity of fat depots as indicated by [ 59 ]. Additionally, a polymorphism in the HSP70.2 gene was also reported to be associated with backfat thickness in pigs [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the HSP70.2 in EM and IC in the present study could be also related to the quantity of fat depots as indicated by [ 59 ]. Additionally, a polymorphism in the HSP70.2 gene was also reported to be associated with backfat thickness in pigs [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Murrah buffaloes have significantly higher levels of HSP70 following dry heat exposure (42 °C with existing relative humidity) than those in control conditions [40]. Based on a study by Jin et al [48], HSP70 genotypes K1-AB and K3-BB have been associated with increased carcass weight and backfat thickness in Korean pigs. The increased expression of HSP70 could have significantly contributed to the ability of pig tissues in preserving the quality and functionality of their proteins, thus demonstrating their remarkable ability to adapt to heat stress with better productivity [41].…”
Section: Heat Shock Protein 70 Polymorphism and Livestock Performancementioning
confidence: 99%
“…There is genetic evidence that sheep [44,45], goats [46], cattle [47], pigs [48] and poultry [49] can adapt to living in heat-stressed environments. When cells undergo extreme heat stress, heat shock factors (HSFs) activate thermo-resistant genes such as HSPs, and their expression increases [50].…”
Section: Heat Shock Protein 70 Polymorphism and Livestock Performancementioning
confidence: 99%
“…Since both μ -and m -calpain have a cysteine residue at their active sites and require reducing conditions that they may infl uence postmortem proteolysis (Ouali et al 2006 ). Several recent studies have demonstrated that HSP are upregulated in postmortem muscle (van Laack et al 1993 ;Bouley et al 2004 ;Hwang et al 2005 ;Jia et al 2006a, b ;Sayd et al 2006 ;Jin et al 2006 ). In a study comparing microarrays between high and low quality meat groups from beef longissimus muscles, the down -regulation of alpha β -crystallin and HSP27 in muscle samples taken at 10 minutes postmortem was associated with improved tenderness, juiciness, and fl avor (Bernard et al 2007 ).…”
Section: Effect Of Oxidation On Calpain -Mediated Proteolysismentioning
confidence: 99%